Nuclear Factor-κB Activating Protein Plays an Oncogenic Role in Neuroblastoma Tumorigenesis and Recurrence Through the Phosphatidylinositol 3-Kinase/Protein Kinase B Signaling Pathway - Liu, Jun; Zhang, Mingyu; Kan, Ying; Wang, Wei; Liu, Jie; Gong, Jianhua; Yang, Jigang (Frontiers in Cell and Developmental Biology, 2021)
Nuclear factor-κB activating protein (NKAP) is a conserved nuclear protein that acts as an oncogene in various cancers and is associated with a poor prognosis. This study aimed to investigate the role of NKAP in neuroblastoma (NB) progression and recurrence. We compared NKAP gene expression between 89 recurrence and 134 non-recurrence patients with NB by utilizing the ArrayExpress database. The relationship between NKAP expression and clinicopathological features was evaluated by correlation analysis. We knocked down NKAP expression in NB1 and SK-N-SH cells by small interfering RNA transfection to verify its role in tumor proliferation, apoptosis, and the phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) signaling pathway. NKAP gene expression in NB tissues was significantly overexpressed in the recurrence group compared with the non-recurrence group, and NKAP was enriched in the PI3K/AKT pathway. Correlation analysis revealed NKAP expression was correlated with chromosome 11q deletion in patients with NB. Knockdown of NKAP expression significantly inhibited the proliferation and promoted the apoptosis of NB1 and SK-N-SH cells. Moreover, we found that small interfering NKAP significantly reduced p-PI3K and p-AKT expression. NKAP knockdown played an oncogenic role in NB by inhibiting PI3K/AKT signaling pathway activations both in vitro and in vivo. Our research revealed that NKAP mediates NB cells by inhibited proliferation and promoted apoptosis through activating the PI3K/AKT signaling pathways, and the expression of NKAP may act as a novel biomarker for predicting recurrence and chromosome 11q deletion in patients with NB.